Investigation of Tribochemical Reactions by Organic Sulfides on Nascent Metal Surfaces - Tomoo Kubo (Japanese Society of Tribologists, 2007)
Under conditions of boundary lubrication, there is direct contact and surface films such as metal oxides and organic contaminants are mechanically removed by mechanical contacts. This causes to form a chemically active nascent surface. It is essential to understand the reaction between lubricant additives and the nascent metal surface. In this research, the well known organic sulfides were selected as the model compounds of extreme pressure additives (EP additives). The catalytic effect of a nascent metal surface without thermal effect was studied using cutting method with a ceramic tip and the reaction was monitored with a quadrupole mass spectrometer. The main result is that the type of alkyl group and the number of sulfur atoms in the central chain (for instance, mono-sulfide or disulfide) have a strong influence on the adsorption and reaction of the sulfide compounds.